2008
DOI: 10.1177/1756283x08093568
|View full text |Cite
|
Sign up to set email alerts
|

Review: Chemoprevention of esophageal adenocarcinoma

Abstract: The incidence of esophageal adenocarcinoma (EAC) is rising rapidly in Western countries, and effective chemoprevention for this malignancy is lacking. Endoscopic surveillance of patients with Barrett's esophagus is currently employed to diagnose EAC at earlier stages, but this strategy has several limitations. Non-steroidal anti-inflammatory drugs and proton pump inhibitors are the most promising agents for prevention of EAC, and a randomized controlled trial of aspirin and esomeprazole is ongoing. Other agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Other authors have reported that antioxidant supplements, such as vitamin C, may also be effective chemopreventive agents for Barrett's patients by protecting against the DCA-induced DNA damage and NF-κΒ activation [52]. The non-steroidal anti-inflammatory COX-2 inhibitors and the application of n-3 fatty acids could also play a chemopreventive role by suppressing the eicosanoid production as further investigators found out [66,67]. With such knowledge, perhaps a new therapy for patients with Barrett's esophagus to prevent the progression to esophageal adenocarcinoma may be the introduction of UDCA to alter the bile acid composition, in combination with the antioxidant vitamin C, COX-2 inhibitors or n-3 fatty acids.…”
Section: The Role Of Acids and Bile Acids In Barrett's Esophagusmentioning
confidence: 95%
“…Other authors have reported that antioxidant supplements, such as vitamin C, may also be effective chemopreventive agents for Barrett's patients by protecting against the DCA-induced DNA damage and NF-κΒ activation [52]. The non-steroidal anti-inflammatory COX-2 inhibitors and the application of n-3 fatty acids could also play a chemopreventive role by suppressing the eicosanoid production as further investigators found out [66,67]. With such knowledge, perhaps a new therapy for patients with Barrett's esophagus to prevent the progression to esophageal adenocarcinoma may be the introduction of UDCA to alter the bile acid composition, in combination with the antioxidant vitamin C, COX-2 inhibitors or n-3 fatty acids.…”
Section: The Role Of Acids and Bile Acids In Barrett's Esophagusmentioning
confidence: 95%
“…Recently, some chemical agents such as proton pump inhibitors (PPIs), nonsteroidal anti-inflammatory drugs (NSAIDs), selective cyclooxygenase-2 inhibitors (COXIBs), green tea, retinoic acid and thioproline have been reported to prevent EAC [22]. We performed several experiments by our rodent model using rabeprazole, thioproline or celecoxib to prevent inflammation-metaplasia-adenocarcinoma (IMA) sequence.…”
Section: Prevention Of Barrett Esophagus and Esophageal Adenocarcinomamentioning
confidence: 99%
“…Accordingly, a number of in vitro and animal studies suggest a possible chemopreventive effect of COX-2 inhibitors in Barrett's mucosa [23] . Cultured cells from Barrett's epithelium, gained by endoscopic biopsies, and treated with a selective COX-2 inhibitor showed a significant decrease in COX-2 expression and in cell proliferation [24] .…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Male gender is an established risk factor for different diseases, including BE and associated adenocarcinoma, possibly due to the lack of the protective effect of estrogen and progesterone that is present in females [23] . However, population-based studies were not able to show a significant association of hormone replacement therapy with the risk of EAC [67,68] .…”
Section: Hormonesmentioning
confidence: 99%